1973
DOI: 10.1093/jaoac/56.5.1281
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Liquid Chromatographic Determination of β-Asarone, A Component of Oil of Calamus, in Flavors and Beverages

Abstract: A method has been developed for the detection and quantitation of β-asarone in vermouths. Volatiles are isolated by steam distillation, and β-asarone is separated from interfering substances by solvent extraction and subjected to gas chromatographic analysis. Quantitation of samples containing 5–100 ppm β-asarone was achieved by direct chromatographic peak comparisons with standards prepared in 20% ethanol-water, which are treated the same as samples. Average recovery from light and dark vermouths spiked at 5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Many previous studies reported a large number of triploid and tetraploid variants with high β-asarone concentrations (i.e., >20% and 75-96%, respectively) in India [12,13,15,16] that cannot be used in medicines or food supplements due to high concentration of…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies reported a large number of triploid and tetraploid variants with high β-asarone concentrations (i.e., >20% and 75-96%, respectively) in India [12,13,15,16] that cannot be used in medicines or food supplements due to high concentration of…”
Section: Introductionmentioning
confidence: 99%
“…The /3-asarone content of the oil derived from the tetraploid variety of Indian Acorus calamus Linn, has been reported to be 82% (Guenther, 1952) while oil from the European variety contains about 5% /3-asarone (Larry, 1973).…”
mentioning
confidence: 99%
“…Column chromatography (Chopra et al, 1965) and gas-liquid chromatography (Larry, 1973;Usseglio-Tomasset, 1966) have been used for the quantitative determination of /3-asarone, while thin-layer chromatog-Food and Drug Administration, 599 Delaware Ave., Buffalo, New York 14202. raphy (TLC) (Stahl, 1965) has been used for the qualitative identification of the components in calamus.…”
mentioning
confidence: 99%